Penguatan Kapasitas Guru Sekolah Menengah Atas Terkait Kemampuan Literasi dan Adaptasi Bencana Erupsi Gunung Merapi - Hafida, Siti Hadiyati Nur; Kesumaningtyas, Mayang Arum; Wijayanti, Alfina (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Indonesia is a country with a high level of volcanic activity, including repeated eruptions of Mount Merapi, which have had an impact on the environment and surrounding communities. In this context, strengthening teacher capacity is essential to improve disaster literacy and adaptation in schools so that it can support student preparedness and resilience in facing disaster risks. The purpose of this community service activity is further to strengthen teachers' understanding of disaster adaptation and literacy. This community service activity further strengthens teachers' understanding of disaster adaptation and literacy skills. Methods: Community service activities use socialization and education methods related to disaster adaptation and literacy skills. In addition, the community service team encourages participants to understand the integration of disaster material in the learning process to encourage increased disaster adaptation and literacy skills. Results: The results of the community service show that after participating in this activity, participants began to understand the importance of integrating disaster material into the learning process because it will be related to 21st-century skills. Participants also realized that through this integration, lifelong learning can be achieved. Conclusion: Disaster material is still very limited in its integration into learning; it is necessary to have an understanding and readiness from each teacher in the field of science to understand and integrate it into every learning activity.